2019
DOI: 10.1108/medar-01-2018-0259
|View full text |Cite
|
Sign up to set email alerts
|

Institutional and economic determinants of corporate social responsibility disclosure by banks

Abstract: Purpose: This article explores the firm's and country-level institutional forces that determine bank's CSR reporting diversity, during the recent global financial crisis (2005-2011). Design/methodology/approach: Drawn on the New Institutional Sociology, it combines Campbell's (2007) institutional theory with Dillard's et al. (2004) model of organizational dynamic change. Specifically, the present article assesses if economic and institutional conditions explain CSR disclosure strategies of thirty listed and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 83 publications
(201 reference statements)
3
31
0
Order By: Relevance
“…Vol. 8(2)(2020): The documents analysed here thus provide further evidence of a process of legitimating convergence, whereby corporate reporting is moving closer to what was previously found only in sustainability reports, interweaving well-being discourse with growth and profitability discourse in a naturalised narrative of mutual compatibility (Oliveira et al, 2019). These texts thereby make a fundamental contribution to furthering the banks' ongoing strategic legitimacy goals.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Vol. 8(2)(2020): The documents analysed here thus provide further evidence of a process of legitimating convergence, whereby corporate reporting is moving closer to what was previously found only in sustainability reports, interweaving well-being discourse with growth and profitability discourse in a naturalised narrative of mutual compatibility (Oliveira et al, 2019). These texts thereby make a fundamental contribution to furthering the banks' ongoing strategic legitimacy goals.…”
Section: Discussionsupporting
confidence: 52%
“…It is perhaps significant that one of the Spanish banks included no references to CSR in its text, and another only incorporated perfunctory references, while the UK banks all devoted at least 12% of the text to CSR issues. Previous comparisons between countries have suggested that countries with more robust banking systems such as the UK have a longer tradition of CSR disclosure and generally disclose more information on this subject (KPMG, 2013;Oliveira et al, 2019), and this may filter down into the focus of the chairman's statement/letter, where space is at a premium. On the other hand, the bank with the greatest percentage of words dedicated to CSR was Spanish, perhaps bearing out Oliveira et al's suggestion concerning Spain, Portugal and Italy (2019: 218), that banks from weaker economies sometimes adopt mimetic behaviours to boost their legitimacy, and in doing so may even overcompensate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chih et al. (2010) and Oliveira et al. (2019) have concluded on the validity of Campbell's theoretical arguments.…”
Section: Hypothesis Developmentmentioning
confidence: 98%